Ultrasound-Guided Physiological Saline Injection for Patients with Myofascial Pain - Kongsagul, Sussaya (J Med Ultrasound, 2019)
BACKGROUND: Based on the histological confirmation of the presence of nerve structure in the fascia, hence, myofascial pain was treated by the mechanism referred to as interfascial block. To date, the studies of physiological saline for treating patients with myofascial pain has been limited. Ultrasound (US) guided with physiological saline injection (PSI) technique has been routinely practiced among patients with myofascial pain in outpatient service at the Department of Rehabilitation Medicine, King Chulalongkorn Memorial Hospital. The main objective of this present study is to find the overview data including the percentage of patients responding, acceptable pain period, and adverse events. MATERIALS AND METHODS: Electronic medical reports among 142 patients receiving US-guided PSI from August 1, 2016, to November 20, 2017, at the Department of Rehabilitation Medicine, King Chulalongkorn Memorial Hospital, were retrospectively reviewed by the first author. Procedures were performed by the last author. The analysis was independently performed by the first author. RESULTS: One hundred and forty-two patients with complete medical records were compatible with analysis. The average age of patients was 55 years. Most of the patients were female (68.3%). Most of the patients (76.8%) had chronic suffering from myofascial pain. Approximately half of the patients (56.4%) are currently received pain-relieving medications. Upper trapezius muscle (19.5%) was the most common muscle receiving the procedure, followed by multifidus (10.0%) and quadratus lumborum (9.5%). Most of the patients (86.8%) received the procedure one muscle. Approximately 30% of the patients were able to stop pain-relieving medications after the procedure. The median of acceptable pain period was 63 days. The percentage of patients having an acceptable pain period >3 months was 43.9%. No major adverse events were demonstrated. CONCLUSION: US-guided PSI technique demonstrated pain reduction in 72.8% of the analyzed patients, with an acceptable pain period of 63 days. No major adverse events were demonstrated among all the patients. This technique should be considered as another invasive procedure for eradication myofascial trigger point.